Feministic approach in the novels of Jane Austen: A Study - Nagar, Dr. Poonam; Agrawal, Dr. Ekta; Jain, Dr. Jitendra (The journal of contemporary issues in business and government, 2023)
Austen explored that individual reform is the way to transform society. Consequently, the paper investigates Jane Austen's ideas and views on women, her education & her liberty of thought, and freedom of expression in society, challenging the notion that women could not learn deeply and exist independently as the themes of her novels. The life of a woman in the nineteenth century has three key facets: Better social standing and financial independence for which they & their family try to seek a well-settled marriage partner, and, rearing and managing the home and the children. From birth to the end of their life, the women remained like dumb animals having no voice to rise against and no freedom to express and take decisions. Thus, the dissertation explores and identifies, how Jane Austen internalized and engaged with the revolutionary ideas of her time and entered the ideological, transplanted empowerment of women through the themes and skills of writings which challenged British society to reconsider the woman's place and her role in their life.